Next‐generation global satellite system with mega‐constellations. (24th July 2020) - Ravishankar, Channasandra; Gopal, Rajeev; BenAmmar, Nassir; Zakaria, Gaguk; Huang, Xiaoling
Summary: Mega satellite constellations in low earth orbit (LEO) will provide complete global coverage; rapidly enhance overall capacity, even for unserved areas; and improve the quality of service (QoS) possible with lower signal propagation delays. Complemented by medium earth orbit (MEO) and geostationary earth orbit (GEO) satellites and terrestrial network components under a hybrid communications architecture, these constellations will enable universal 5G service across the world while supporting diverse 5G use cases. With an unobstructed line‐of‐sight visibility of approximately 3 min, a typical LEO satellite requires efficient user terminal (UT), satellite, gateway, and intersatellite link handovers. A comprehensive mobility design for mega‐constellations involves cost‐effective space and ground phased‐array antennas for responsive and seamless tracking. An end‐to‐end multilayer protocol architecture spanning space and terrestrial technologies can be used to analyze and ensure QoS and mobility. A scalable routing and traffic engineering design based on software‐defined networking adequately handles continuous variability in network topology, differentiated user demands, and traffic transport in both temporal and spatial dimensions. The space‐based networks involving mega‐constellations will be better integrated with their terrestrial counterparts by fully leveraging the multilayer 5G framework, which is the foundational feature of our hybrid architecture. Abstract : Mega satellite constellations in low earth orbit will provide complete global coverage; rapidly enhance overall capacity, even for unserved areas; and improve the quality of service (QoS) possible with lower propagation delays. Complemented by medium earth and geostationary orbit satellites, and terrestrial network components under a hybrid communications architecture, these constellations will enable universal 5G service and diverse use cases across the world with QoS for differentiated traffic, supported by end‐to‐end multilayer protocol, mobility and routing designs.